Factors Affecting The Qualıty Of Work Life Of Nurses: Example Of Balıkesir - Soner Ayaz; Kerime Derya Beydağ (Association of Nurse Managers, 2014)
OBJECTIVE: The aim of this study to determine the factors affecting the work quality which improves depending on the working conditions of the nurses. METHODS: The universe of sectional-descriptive study consists of 665 nurses working at the hospitals affiliated to Balikesir City Public Hospitals Association; in the cases in which the universe is clear 338 nurses (50.8%) are included to the study as the sample group by using the sample calculation formula. After getting the required permissions, 16 questionnaires aiming to determine the demographic and professional characteristics are conducted between June-October 2013 and Work Life Quality Scale of Nursing, which is improved by Brooks (2007) and translated into Turkish by Şirin (2011) and whose validity and reliability is approved, has been achieved. In the evaluation of the data number and percentage calculations, Man-Whitney U test, Kruskal -Wallis test, Pairled -Sample t-test and ANOVA test was used. RESULTS: The total score average of "Quality of Nursing Work Life Scale" (HİYKÖ) for nurses in the study is found to be 101.95 +- 22: 15. CONCLUSION: Age group, marital status, having children, educational status, length of employment, weekly working hours, working status, the period they want to work at the institution of the nurses and the HİYKO total score are statistically and significantly different (p > 0.05). Between nurses' gender, the institutions they work, tasks, place of employment, type of work, number of shifts, the certification / training programs they participated in, working according to their special education/certification/field of expertise, being offered a promotion and the HİYKÖ total score, some statistically significant differences were observed (p < 0.05).